Using integrative bargaining to achieve mutually beneficial agreements - Menkel-Meadow, Carrie (Henry Stewart Talks, 2011)
Why do we bargain and negotiate?, How do we negotiate?, Conventional approach: compete to win, Integration in negotiation, Needs and interests, The other way: negotiate to integrate, Thinking out of the box, How do we integrate?, Contexts that affect our efforts to integrate, Ways to integrate in negotiation, Successful integrative bargaining